The analysis of overall survival and estimation of survival prognostic factors in patients diagnosed with renal cancer metastases to lymph nodes - D. V. Semyonov; R. V. Orlova; V. I. Shirokorad; S. V. Kostritsky (Вестник урологии, 2025)
Introduction. The comprehensive analysis of prognostic factors influencing survival outcomes in patients with renal cell carcinoma (RCC) and metastatic lymph node (LN) involvement represents a critical component for evidence-based decision-making in clinical practice and the development of personalized treatment strategies.Objective. To systematically identify and evaluate prognostic factors impacting overall survival (OS) in patients diagnosed with lymph node metastases of renal cell carcinoma.Materials & methods. A comprehensive retrospective analysis was conducted on a cohort of 332 patients with RСС metastases to LN, who received treatment at the Moscow City Oncological Hospital No. 62 and St. Petersburg City Clinical Oncological Dispensary between 2006 and 2022. The patient population was stratified into prognostic groups as follows: 110 patients (33.0%) were categorized into the intermediate prognosis group, while 160 patients (48.0%) were classified into the unfavourable prognosis group. The study systematically evaluated clinical and morphological prognostic factors that potentially influence OS indices in patients with RCC metastases to LN.Results. The 3-year and 5-year OS rates in patients with RCC metastases to LN (n = 332) were 35% (95% CI 27 to 44) and 21% (95% CI 15 to 29), respectively, with a median OS of 21.9 months (95% CI 14.9 to 29.9). Univariate analysis revealed several factors with a statistically significant negative impact on OS in patients with RCC metastases to LN: 1) ECOG performance status (p < 0.001), tumour histological subtype (p < 0.001), tumour differentiation according to Fuhrman grading (p < 0.001), type of metastases (p < 0.001), bone metastases (p = 0.001), liver metastases (p < 0.001), IMDC prognostic score (p < 0.001), nephrectomy (p < 0.001), metastasectomy (p < 0.001). Multivariate analysis identified the following independent predictors of poor OS: tumour histological subtype (OR 1.50; 95% CI 1.01 to 2.23), tumour differentiation grade according to Fuhrman (OR 1.74; 95% CI 1.00 to 3.03), IMDC prognostic score (OR 2.60; 95% CI 1.46 to 4.62), nephrectomy (OR 2.39; 95% CI 1.51 to 3.79), metastasectomy (OR 0.61; 95% CI 0.39 to 0.95).Conclusion. In patients with renal cell carcinoma (RCC) metastases to lymph nodes, several key factors have been identified as adverse predictors of survival: histological subtype of RCC, degree of tumour differentiation according to Fuhrman grading, IMDC prognostic score, nephrectomy, metastasectomy. These findings underscore the necessity for further comprehensive research to elucidate additional prognostic factors. Such investigations are essential for enhancing the efficacy of personalized treatment strategies and ultimately improving OS outcomes in patients with RCC.